The muddled concept of life: from Lebensphilosophie to hermeneutic phenomenology in Heidegger’s earliest University lecture : From Lebensphilosophie to Hermeneutic Phenomenology in Heidegger’s Earliest University Lecture - Masís, Jethro (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2024)
A century ago, Heidegger —then Husserl’s scientific assistant— delivered at the University of Freiburg a lecture entitled The Idea of Philosophy and the Problem of Worldview on the War Emergency Semester (Kriegsnotsemester). From our contemporary viewpoint, the lecture is not only important for historical reasons, but rather because of its combative and radical tone regarding the muddled concept of life in philosophy. Heidegger’s definition of phenomenology as originary pre-theoretical science redefines the scope of phenomenological research and prepares the path for its hermeneutical transformation. The lecture serves as testimony of the development of Heidegger’s own philosophical voice, as early as the very beginning of his teaching career, but also untangles the rather confusing underpinnings that plagued Lebensphilosophie since the late 19th century.